Urban development problems in the Algerian city - SAHBI, Ouahiba (Social Sciences Journal)
This article deals with urban development issues in general and the one tha tconcerns the Algerian city in particular takingintoac countit’s social, economic and cultural specialities tha tdifferentia teitfrom the other societies ,and thisrequires development programs that respect the fundamentals and the social and the cultural environment of the urban reality and all the structural problems of the Algerian urban society.